Cellular Zinc Trafficking: the Zinc Proteome and Its Reactions with Cadmium - (:unkn) unknown (My University, 2014)
Metals play a crucial role in living systems. Iron, zinc, copper, molybdenum, and manganese are involved in many essential biological activities. Among transition metals, zinc after iron is the most abundant transition metal in the human body and the most abundant in the brain. It exists in more than 3000 proteins, which comprise about 10% of the human proteome. Zn2+ dyshomeostasis is associated with chronic diseases such as metabolic syndrome, diabetes and related complications, bone loss, growth retardation in young children, and neurological and behavioral problems. Despite a good knowledge obtained for metabolism of some metal ions such as copper, our understanding about Zn2+ trafficking still remains immature. External or internal metal ions, which are chemically similar to Zn2+ may disrupt or interfere with the process of Zn2+ trafficking and make complications. Metallothionein (MT) and the proteome, two major players of cell Zn2+ trafficking, and their metal binding and metal exchange reactions with different ligands were studied in this research. Metallothionein, a small protein molecule rich in cysteine, binds to seven Zn2+ ions with a stability constant of about 1011. A previous study, on the other hand, has reported that one of the seven Zn2+ ions binds to MT with a relatively weak binding constant of 108. Purified Zn7-MT extracted from rabbit liver under neutral conditions (pH 7) was reacted with different competing ligands and did not exhibit such a weak binding affinity to Zn2+ ion. Reaction of Zn7-MT with strong acid resulted in the formation of MT* species, which was converted into Zn7-MT* upon neutralization and reaction with 7 Zn2+ ions. Zn7-MT* exhibited a reactivity of 1 Zn2+ per MT molecule with chelating agents of modest affinity for Zn2+ ion. Titration of Zn7-MT with acid to pH 2 or below produced Zn7-MT*, which exhibited a biphasic titration curve upon base titration demonstrating the binding of 1 Zn2+ ion per MT molecule weakly between pH 5 and 7. Because MT generally undergoes acidification during preparation, care must be taken to document which form of the protein is present in subsequent experiments at pH 7. Zn-proteome as another significant player in Zn2+ trafficking was studied. It has been hypothesized that Zn-proteome has a measurable capacity to bind to metal ions such as Zn2+ or Cd2+ through metal ion exchange chemistry. To test this hypothesis the Zn-proteome of pig kidney LLC-PK1 cells was reacted with competing ligands such as Zinquin acid (ZQACID), TSQ, EDTA, and apo-MT, exhibiting negligible metal exchange reactivity. Reaction of Cd2+ or Zn2+ with the Zn-proteome shows that Cd2+ or Zn2+ associates with the proteome and almost stoichiometric amounts of Zn2+ become available to react with these chelating agents. The results strongly support the hypothesis that Cd2+ displaces Zn2+ from native proteomic binding sites resulting in the formation of Cd-proteome*Zn species. Mobilized Zn2+ adventitiously binds to the proteome and becomes available to react with the metal binding ligands. Cd-proteome and Zn-metallothionein exchange metal ions that increase the possibility that this reaction may recover the functionality to the Cd-protein. Proteome and supernatant from LLC-PK1 cells were titrated with Zn2+ in the presence of zincon (ZI), a relatively weak competing ligand, to study the role of Zn-bound proteome in Zn2+ trafficking . Titration curves confirmed that a significant amount of unoccupied sites exist within the proteome to bind to metal ions. The smaller slope in the second part of the curve compared with the one obtained in the titration of ZI with Zn2+ along with the red-shifted absorbance spectrum indicate that the formed species are different form Zn-ZI species. We hypothesize that these species are ternary adduct complexes, proteome-Zn-ZI. Model proteins such as CA, BSA, and trypsin and the fluorescent ligand, TSQ, were employed to further investigate this hypothesis. BSA reacted with Zn-ZI and the resulted absorbance spectra exhibited a shift in λmax from 620 nm to 640 nm. Furthermore, no Zn2+ was released from the product upon size exclusion chromatography, indicative of adduct complex formation. In contrast, two other proteins, carbonic anhydrase and trypsin did not show any reaction with Zn-ZI indicated by lack of change in λmax in their absorbance spectra. The former is a Zn-protein without unoccupied Zn2+ binding sites and the latter has neither Zn2+ nor documented Zn2+ binding sites. Reaction of TSQ with Zn-ZI also resulted in an emission spectrum with a λmax at 470 nm, characteristic of adduct complex formation.
Keywords: Cadmium; Proteome; Zinc; Zinc Trafficking